Respuesta :

Zezima

Answer:

154

Step-by-step explanation:

The expression is  [tex]f(x)=4x^2-7x+7[/tex] and we know that  [tex]f(x)=f(7)[/tex]. Therefore, you will have to substitute x with 7.

Calculations:

[tex]f(x)=4x^2-7x+7[/tex]

[tex]f(7)=4(7)^2-7(7)+7[/tex]

[tex]4(49)-49+7= 154[/tex]

Answer:

I think that you need to plug 7 in to the x's

Step-by-step explanation:

Yes it looks very weird, but if you don't think that is right, Use the 7 for the F's.

One of them should come out right. :3